Putusan Verstek Terhadap Perkara Perceraian di Pengadilan Agama Sungguminasa Kelas 1 B - Jamiah Tompo; Nurhalifah Nurhalifah; Yusri Muhammad Arsyad (Universitas Muslim Indonesia, 2022)
Marriage is a physical and spiritual relationship between a man and a woman as a couple who fully intends to form a happy and eternal family in the sight of God Almighty. With that there is a problem between the spouses and cannot be resolved by the second perpetrator, there is no longer any assumption until then one of the spouses or wives can apply in court. This research is a type of field research that is qualitative in nature with observation, interviews, and documentation techniques. The analytical method used in this research is using qualitative descriptive analysis techniques. This study aims to determine the verstek decision on divorce cases at the Sungguminasa Religious Court. As the results of the research, the author analyzes from what is obtained that the judge's considerations in the Verstek decision are in accordance with the applicable law in the provisions contained in Article 149 RBg/Article 125 HIR. The form of legal protection for the disputing parties is for the plaintiff if the arguments for the lawsuit are clear and have legal grounds, the lawsuit can be granted without the presence of the defendant. As for the defendant, the verstek decision was notified and informed that he had the right to give resistance (verzet) within 14 days after the verstek decision was delivered to the defendant.